Entre criollos y modernos: género, raza y modernidad criolla en el proyecto editorial de la revista Variedades (Lima, 1908-1919) - Espinoza, Juan Miguel (2015)
This article analyzes gender stereotypes in the discourse of Lima’s Variedades magazine during its first stage (1908-1919), in a context of political and cultural modernization in Peru. The male and female role models promoted byVariedades were part of an inclusive discourse according to which all men and women could contribute to national progress, as long as they were willing to become «modern». The latter served to link modern values to local popular tradi- tions: while asserting the cultural superiority of the white (criollo) modernized elite, it opened possibilities for integrating the indigenous and Afro-descendant populations into national life.